(untitled) (Bangladesh Journal of Nuclear Medicine, 2021)
Objectives: In patients with suspicious bone metastasis, differential diagnosis and primary lesion identification is very important in optimizing treatment planning. The study was aimed to assign a step-wise approach based on image findings to identify the precise role of PET-CT in these patients. Patients and Methods: A total of 74 patients were enrolled with suspicious bone metastasis who underwent PET-CT for the evaluation of primary focus. Patients were classified into four groups with stepwise manners, firstly based on FDG positivity of bone lesions, then on multiplicity of positive bone uptake and finally on presence of extra-skeletal uptake. We analyzed the difference of distribution of follow-up results according to each group. In addition, we also investigated whether PET-CT had a role to guide biopsy sites. Results: Except for 7 patients without bone or extra-skeletal uptake, 44 patients were categorized in multiple bone and extra-skeletal uptake group (A), 12 in multiple bone uptake without extra-skeletal uptake group (B), 3 in single bone and extra-skeletal uptake group (C) and 8 in single bone uptake without extra-skeletal uptake group (D). In group A, 42/44 patients had metastatic bone disease; where primary lesion was correlating extra-skeletal uptake in 40 (91.0%) cases. Among the 12 patients of group B, 5 (41.7%) had primary malignant bone disease, 3 (25.0%) had benign bone lesions and 4 (33.3%) had metastatic bone disease but PET-CT failed to indicate the primary site. In group C, PET-CT positive extra-skeletal uptake sites were confirmed as primary lesions in all the 3 patients. Among the 8 patients of group D, 5 (62.5%) were benign bone disease, one (12.5%) was high grade sarcoma and the remaining two (25.0%) were metastatic bone disease where PET-CT failed to identify primary site. Additionally, there was significant (P = 0.0003) difference in prevalence of biopsy sites performed according to the presence of extra-skeletal uptake in PET-CT. Conclusion: Clinical impact of PET-CT was different according to groups classified with stepwise manners, which suggested that different strategies should be taken especially when there was not extra-skeletal uptake to optimize management plan. PET-CT also had a significant role in patients with extra-skeletal uptake lesion through guidance of easily approachable biopsy sites. Bangladesh J. Nuclear Med. 22(2): 95-102, Jul 2019